The Effect of Loan To Deposit Ratio on Return On Assets at PT. Permata Bank, TBK Period 2010-2020 - Ginting Gerinata (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
This study aims to determine the effect of the Loan to Deposit Ratio on Return on Assets at PT. Permata Bank, Tbk. The method used is explanatory research. The analysis technique uses statistical analysis with regression, correlation, determination, and hypothesis testing. The results of this study, the Loan to Deposit Ratio variable, obtained an average value of 83.73%. The Loan to Deposit Ratio variable received an average value of 2.68%. Loan to Deposit Ratio has a positive and significant effect on Return on Assets with a regression equation value of Y = -6.493 + 0.110X. A correlation coefficient value of 0.747 or has an extreme relationship level with a correlation coefficient level determination value of 55.8%. Hypothesis testing obtained a significance of 0.000 <0.05.